Numerical Analysis of Battery Thermal Management System of Electric Vehicle - Inn, Lai Qit; Oumer, A. N.; Azizuddin, Abd Aziz; Siregar, Januar Parlaungan; Cionita, Tezara (Semarak Ilmu Publishing, 2023)
This study is modelling the direct liquid cooling system of battery used in Electric Vehicle. The purpose of the study is to investigate the performance of the Li-ion battery model under different input of parameters and to evaluate the optimum parameters for the battery thermal management system model to maintain at its peak performance. SolidWorks and ANSYS are used to model and simulate the battery whereas MINITAB software is selected for conducting the statistical analysis. Heat flux, mass flow rate at the inlet and the thickness of the battery model has been selected as input of the simulation. The obtained results show that the heat transfer coefficient is increasing with the higher heat flux and mass flowrate but decreasing with the thickness of the battery model. Pressure drop remains constant when heat flux varies but increasing with mass flow rate and inversely proportional with the thickness of battery. For statistical analysis, an optimum value for the parameters is proposed to maintain the battery to operate with a highest heat transfer coefficient but lowest in pressure difference. Overall, the study has been conducted successfully and fulfilled the objectives stated.